Apollo 12-- On the ocean of storms - Harland, David M. (David Michael) 1955- (Springer Praxis Books, 2011)
With its two moonwalks, deployment of a geophysical station and geological sampling, Apollo 12 did what many had hoped would be achieved by the first men to land on the Moon. It spectacularly demonstrated the precision landing capability required for the success of future lunar surface explorations. Apollo 12 - On the Ocean of Storms contains over 30 page of color images, including high-resolution scans recently produced by NASA from the original Hasselblad film; covers the mission from its planning through to completion; includes conversations among the crew in the spacecraft that were not transmitted; in the definitive 'popular' account of this mission. This is the first time in 40 years that the story of the Apollo 12 mission to the Moon has bene told in its entirety, using official documents, flight transcripts, and post-mission debriefing to recreate the drama.